Decomposition and/or hydrogenation of hydrogen peroxide over Pd/Al2O3 catalyst in aqueous medium: factors affecting the rate of H2O2 destruction in presence of hydrogen - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Hydrogen peroxide destruction by its decomposition and/or hydrogenation to water in the presence of H-2 over Pd(5 wt.%)/Al2O3 catalyst in an aqueous reaction medium, similar to that used in the H-2-to-H2O2 oxidation, has been thoroughly investigated at different reaction conditions. The H2O2 destruction is strongly influenced by the oxidation state of Pd in the catalyst and also by the presence of different halide anions (viz. F-, Cl-, Br- and I-) in the acidic aqueous medium or in the catalyst, depending upon the concentration of halide anions. The cations associated with halide anions have, however, a little or no influence on the H2O2 destruction. The iodide anions strongly poisoned the catalyst, even at their very low concentration. The fluoride anions have only a small effect on the H2O2 destruction. The chloride or bromide anions drastically inhibit the rapid H2O2 decomposition, but promote the slower H2O2 hydrogenation. The H2O2 destruction reactions are strongly influenced by the halide anion and acid concentrations. The presence of acid (protons) plays a very important role in drastically reducing the H2O2 destruction, particularly in the presence of chloride anions. Both in the presence and absence of Cl- or Br- anions, the H2O2 destruction activity of the catalyst is markedly reduced because of the oxidation of Pd but it is drastically increased due to the presence of H-2. A plausible reaction mechanism for the rapid H2O2 decomposition and slower H2O2 hydrogenation reactions, prevailing under the different reaction conditions, has also been discussed. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: decomposition of H2O2; halide anions as catalyst promoter or indicator; Hydrogen peroxide; hydrogenation of H2O2; Pd/Al2O3

Direct oxidation of H-2 to H2O2 over Br and F-promoted Pd/Al2O3 in aqueous acidic medium: influence of the concentration of Br and F and the method of incorporation of the two halogens in the catalyst on their beneficial synergetic effect on the net H2O2 - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2007)
Influence of the addition of F (0-1.1 mmol/g) in the pre-brominated Pd/Al2O3 (Br loading = 0.13 mmol/g) and also that of Br (0.13 mmol/g) in the pre-fluorinated Pd/Al2O3 (F loading = 0.53 mmol/g) on the net H2O2 formation in the H-2-to-H2O2 oxidation (with H-2/O-2 mole ratio of 1.0) over the halogenated catalysts in aqueous acidic (0.1 M H3PO4) medium have been investigated. In both the cases, the highest synergetic effect (resulting in the highest net H2O2 formation) produced by the addition of other halogen is observed at its optimum concentration (viz. 0.13 mmol Br/g in the fluorinated Pd/Al2O3 and 0.13 mmol F/g in the pre-brominated Pd/Al2O3). The beneficial synergetic effect of the two halogens is also found to be strongly influenced by the way of incorporation of the two halogens in the catalyst. The enhancement in the net rate of H2O2 formation due to the synergetic effect for the different methods of Pd/Al2O3 halogenation is in the following order: simultaneous bromination and fluorination < first fluorination and then bromination < first bromination and then fluorination. The fluorination (at optimum concentration of 0.13 mmol F/g) of the pre-brominated (0.13 mmol Br/g) Pd/Al2O3 led to the best catalyst for the H-2-to-H2O2 oxidation with 100% H-2 conversion and 78% H2O2 yield/selectivity. The destruction of H2O2 by its decomposition and/or hydrogenation over the halogenated catalysts has also been studied. (c) 2007 Published by Elsevier B.V.
Keywords: F and Br-promoted Pd/Al2O3; Hydrogen peroxide; oxidation of H-2-to-H2O2; synergetic effect of F and Br

Direct oxidation of hydrogen to hydrogen peroxide over Pd (or PdO)/Al2O3 in aqueous reaction medium: influence of different acids and halide anions in reaction medium on formation and destruction of H2O2 - Choudhary, Vasant R.; Ingole, Yugesh V.; Samanta, Chanchal; Jana, Prabhas (Industrial & Engineering Chemistry Research, 2007)
Effects of different mineral acids (viz. H2SO4, H3PO4, HNO3, HCl, HBr, and HI), acid (H3PO4) concentration, different halide anions (viz. F-, Cl-, Br-, and I-), and halide anion concentration in aqueous reaction medium on the H2O2 formation (in H-2-to-H2O2 oxidation) and/or on the H2O2 destruction (by H2O2 decomposition and hydrogenation) activities of Pd (or PdO)/Al2O3 catalyst (at 300 K and atmospheric pressure) have been thoroughly investigated. Among the different halide anions, Br- anions are most effective for promoting the H2O2 formation and inhibiting the H2O2 destruction by both the H2O2 decomposition and/or hydrogenation. The cations associated with the halide anions, however, have only a little or no influence on both the H2O2 formation and destruction. The concentration of the different halide anions has a strong influence on the H-2 conversion and H2O2 formation and destruction activities of the Pd/Al2O3. The H2O2 formation activity in the presence of Br- or Cl- anions is highest at the optimum concentration of halide (about 1.0 mmol/dm(3)). it is also highest at the optimum concentration of phosphoric acid (between 0.1 and 0.3 mol/dm(3)). In general, the H2O2 formation is increased with decreasing the H2O2 destruction activity of the catalyst, indicating a close relationship between the two. Br- anions act as an excellent catalyst promoter for Pd/Al2O3 catalyst, but they show only a small promoting effect for PdO/Al2O3 catalyst. The next choice for halide promoter for Pd/Al2O3 catalyst is Cl- anions. F- and I- anions are, however, catalyst inhibitor and strong poison, respectively, for the H2O2 formation. At the same concentration, Br- anions are more effective than Cl- anions for inhibiting the H2O2 destruction reactions over Pd/Al2O3 Catalyst. For both halide promoters (Cl- and Br-), the net H2O2 formation is controlled by the H2O2 hydrogenation rather than by the H2O2 decomposition.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Direct H(2)-to-H(2)O(2) oxidation in aqueous acidic medium containing Br promoter over Pd/Al(2)O(3) and Pd/C catalysts thermally pretreated under different conditions - Choudhary, Vasant R.; Jana, Prabhas; Bhargava, Suresh Kumar (Catalysis Letters, 2008)
Influence of thermal pretreatments (under N(2), air or H(2) gas atmosphere at 500 degrees C or 700 degrees C) has been investigated for the Pd/Al(2)O(3) and Pd/Carbon catalysts in terms of its effect on their Pd particle size and performance in the H(2)-to-H(2)O(2) oxidation and H(2)O(2) destruction (by decomposition and/or hydrogenation) reactions in aqueous acidic medium containing Br promoter. The influence on the net H(2)O(2) formation is found to depend strongly upon the catalyst support due to support-Pd cluster interactions. For both the catalysts, the thermal treatments (except in air) caused a large increase in their Pd particle size. The increase in Pd particle size caused an increase in the H(2)O(2) formation activity of Pd/Al(2)O(3) but a decrease in the H(2)O(2) formation activity of Pd/C.
Keywords: Hydrogen peroxide; oxidation of H(2) to H(2)O(2); Pd/Al(2)O(3); Pd/C

Direct oxidation of H-2 to H2O2 over different supported PdO catalysts in aqueous acidic medium: Influence of the reduction, calcination temperature and support of the catalyst on its net H2O2 formation activity - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2008)
Effects of the catalyst reduction (by hydrazine), calcination temperature (400-800 degrees C) and support (viz. Al2O3, SiO2, CeO2, ZrO2, HP or HM) on the performance of supported PdO (2.5 wt%) catalyst in the H-2-to-H2O2 oxidation (with H-2:O-2 = 1: 1) in an aqueous acidic (0.1 M H3PO4) medium under ambient conditions have been investigated. All the supported PdO catalysts showed lower H2 conversion activity, but higher H2O2 selectivity, as compared to their reduced counter parts. The catalyst performance for the net H2O2 formation is strongly influenced by both the support and calcination temperature of the supported PdO catalysts. The catalysts calcined at 400 degrees C showed better performance. Among the catalysts, PdO/Al2O3 catalyst (calcined at 400 degrees C) showed the best performance (17.0% H2O2 yield) in the H-2-to-H2O2 oxidation. The influence of the calcination temperature of PdO/Al2O3 catalyst on its H2O2 decomposition and hydrogenation activities has also been investigated. Both the H2O2 decomposition and hydrogenation activities increased with increasing the calcination temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrogen peroxide; oxidation of H-2 to H2O2; supported PdO catalysts

Direct oxidation of H-2 to H2O2 over PdO/Al2O3 catalysts in aqueous acidic medium: influence on H2O2 formation of Pd loading, calcination temperature and reduction of catalyst and presence of halide anions - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2008)
Effects of the Pd loading (0.2-10 wt%), calcination temperature (400-900 degrees C) and reduction of PdO/Al2O3 on its performance in the H-2-to-H2O2 oxidation (with H-2/O-2 = 1:1) in an aqueous 0.1 M H3PO4 medium, in the absence and presence of different halide anions, under ambient conditions have been investigated. The effect of calcination temperature on the H2O2 formation varied depending upon the Pd loading. The influence of the different halide anions was found to depend strongly on the nature of halide anion (F-, Cl-, Br- or I-) and the oxidation state of Pd and its loading in the catalyst. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: halide catalyst promoters; Hydrogen peroxide; oxidation of H-2 to H2O2; Pd/Al2O3; PdO/Al2O3

Direct H-2-to-H2O2 oxidation over highly active/selective Br-F-Pd/Al2O3 catalyst in aqueous acidic medium: Influence of process conditions on the H2O2 formation - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2009)
The influence of the O-2/H-2 mote ratio in the gaseous feed and also those of other reaction conditions [viz. concentration of H3PO4 (0-5 mol/dm(3)). temperature (5-50 degrees C, gas (H-2 and O-2) space velocity (5.8-23.4 h(-1)) and reaction time (0.1-8 h)] on the H2O2 formation in the H-2-to-H2O2 oxidation over the Br(1 wt%)-F(1 wt%)-Pd(5 wt%)/Al2O3 catalyst in an aqueous acidic (H3PO4) medium have been thoroughly investigated. The effects of the O-2/H-2 ratio, reaction temperature and acid concentration on the destruction of H2O2 by its decomposition and/or hydrogenation reactions over the catalyst in the acidic reaction medium have also been studied. The net H2O2 formation (H2O2 yield) over the catalyst passed through a maximum with increasing the acid concentration, the temperature or the O-2/H-2 feed ratio. However, it decreased markedly with increasing the gas space velocity or the reaction period. The H2O2 decomposition and hydrogenation activities of the catalyst increased appreciably with increasing the reaction temperature and decreased with increasing the acid concentration. The H2O2 destruction during the H-2-to-H2O2 oxidation increased with increasing the concentration of H-2 (relative to that of O-2) due to the increased H2O2 hydrogenation rate over the catalyst. The net H2O2 formation in the H-2-to-H2O2 oxidation decreased sharply with increasing the initial amount of H2O2 present in the reaction mixture. The presence of H2O2 and the higher H-2/O-2 ratios have detrimental effects on the net formation of H2O2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Br-F-Pd/Al2O3 catalyst; H2O2 decomposition; H2O2 hydrogenation; hydrogen oxidation; Hydrogen peroxide